2007
DOI: 10.1016/j.abb.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

A novel function of VCP (valosin-containing protein; p97) in the control of N-glycosylation of proteins in the endoplasmic reticulum

Abstract: Summaryα chain of T-cell receptor (TCR) is a typical ERAD (ER-associated degradation) substrate degraded in the absence of other TCR subunits. Depletion of derlin1 fails to induce accumulation of αTCR despite inducing accumulation of α1-antitrypsin, another ERAD substrate. Furthermore, while depletion of VCP does not affect levels of α1-antitrypsin, it induces an increase in levels of αTCR. RNAi of VCP induces preferential accumulation of αTCR with less mannose residues, suggesting its retention within the ER.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
(97 reference statements)
2
4
0
Order By: Relevance
“…Similarly, S2′ derived from QQ p97 over-expressing P1 displayed reduced levels of deglycosylated TCRα when compared to those from untransfected and WT p97 controls (Figure 3D, top panel, compare lane 9 to 8 and 7). Consistent with previous reports, these findings not only demonstrate that QQ p97 over-expression can functionally inactivate retro-translocation, but also indicate an important role of p97 activity in the formation of deglycosylated TCRα in cells [32][34]. Surprisingly, when mock- and p97-depleted CE were incubated with an untransfected P1, the levels of deglycosylated TCRα in the resulting S2′ fractions were unaffected (Figure 3E, top panel, compare lane 2 to 1).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, S2′ derived from QQ p97 over-expressing P1 displayed reduced levels of deglycosylated TCRα when compared to those from untransfected and WT p97 controls (Figure 3D, top panel, compare lane 9 to 8 and 7). Consistent with previous reports, these findings not only demonstrate that QQ p97 over-expression can functionally inactivate retro-translocation, but also indicate an important role of p97 activity in the formation of deglycosylated TCRα in cells [32][34]. Surprisingly, when mock- and p97-depleted CE were incubated with an untransfected P1, the levels of deglycosylated TCRα in the resulting S2′ fractions were unaffected (Figure 3E, top panel, compare lane 2 to 1).…”
Section: Resultssupporting
confidence: 91%
“…In agreement with previous reports [32][34], p97 catalyzes an important step in TCRα retro-translocation and degradation. Specifically, expression of an ATPase-defective p97 mutant decreased appearance of deglycosylated TCRα species in both membrane as well as in vivo and in vitro cytosolic fractions.…”
Section: Discussionsupporting
confidence: 93%
“…Complementation of the HTM1 (EDEM) or Cdc48 (VCP) deficiency in yeast cells by the mammalian orthologue EDEM or VCP underlines the necessity of these proteins in CFTR degradation and highlights the similarity of quality control and ERAD in yeast and mammals [45]. A novel function of VCP in the control of N-glycosylation of proteins in the ER was recently demonstrated [46].…”
Section: Role Of Vcp In Er and Post-er Compartmentsmentioning
confidence: 98%
“…Complementation of the HTM1 (EDEM) or Cdc48 (VCP) deficiency in yeast cells by the mammalian orthologue EDEM or VCP underlines the necessity of these proteins in CFTR degradation and highlights the similarity of quality control and ERAD in yeast and mammals [45]. A novel function of VCP in the control of N‐glycosylation of proteins in the ER was recently demonstrated [46]. Mass spectrometric analysis of cellular N‐linked glycans revealed that depletion of VCP decreases the level of high‐mannose glycoproteins, increases the levels of truncated low‐mannose glycoproteins and induces changes in the abundance of complex glycans assembled in post‐ER compartments.…”
Section: Role Of Vcp In Er and Post‐er Compartmentsmentioning
confidence: 99%
“…It has been shown that this deglycosylation enzyme is involved in ERAD and cleaves N-glycans from misfolded glycoproteins during their proteasomal degradation [5][6][7][8]. In mammalian cells, some ERAD substrates are presumed to be deglycosylated by the PNGase during the degradation process [7,9,10]. In budding yeast Saccharomyces cerevisiae, a ricin toxin A-chain non-toxic mutant (RTAΔ) and its transmembrane protein derivative, RTL (RTAΔ-transmembrane-Leu2), have been identified as Png1-dependent ERAD substrates [6][7][8]11].…”
Section: Introductionmentioning
confidence: 99%